Linking Flexible Working Arrangement and Employee Performance in Post-pandemic Era: Mediating Role of Motivation - Hutabarat, Claudya Caprieta (Journal of Sustainable Community Development (JSCD), 2023)
In a world characterized by evolving work paradigms and changing employee expectations, the adoption of flexible working arrangements has gained prominence across various industries including financial services. However there has been limited study exploring the dynamic interplay between flexible working arrangements and employee performance, with a specific focus on the mediating role of motivation. This study aims to unravel how flexible work arrangements influence employee performance, and how motivation serves as a crucial mechanism in this relationship. By examining the connections between these variables, the research seeks to contribute to a more comprehensive understanding of the modern workplace landscape. The research is a quantitative study, analyzed using structural equation modeling (SEM) that was conducted using SmartPLS4 and a purposive sampling technique. The data were collected from 113 employees working in financial services companies in Greater Jakarta Area. The results found that FWA have significant effect on employee performance and so does motivation on employee performance. Although, as in mediating role, the findings in this study show that motivation does not mediate the relationship between FWA and employee performance. Keywords: Flexible Working Arrangement, Employee Performance, Motivation, Financial services industries, Post-pandemic.